2019
DOI: 10.1016/j.gaitpost.2019.07.192
|View full text |Cite
|
Sign up to set email alerts
|

Knee adduction moments are not increased in obese knee osteoarthritis patients during stair negotiation

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Past studies have demonstrated increased TF joint loading during walking with obesity 38e40 , and reductions in joint compressive loading with weight loss 41 . This year Verlaan et al 42 provided further evidence, showing that obese individuals with OA exhibited more flattened KAM patterns and increased stance times during stair ascent, indicative of more constant total knee loading with obesity. These results are consistent with past evidence of more constant KAM loading patterns 43 reported during walking in obese individuals with knee OA, characteristic of the gait patterns linked to clinical TF OA progression by Hatfield et al 19 This highlights a potential link between altered mechanics with obesity and clinical TF progression.…”
Section: Biomechanics and Osteoarthritis Progressionmentioning
confidence: 95%
“…Past studies have demonstrated increased TF joint loading during walking with obesity 38e40 , and reductions in joint compressive loading with weight loss 41 . This year Verlaan et al 42 provided further evidence, showing that obese individuals with OA exhibited more flattened KAM patterns and increased stance times during stair ascent, indicative of more constant total knee loading with obesity. These results are consistent with past evidence of more constant KAM loading patterns 43 reported during walking in obese individuals with knee OA, characteristic of the gait patterns linked to clinical TF OA progression by Hatfield et al 19 This highlights a potential link between altered mechanics with obesity and clinical TF progression.…”
Section: Biomechanics and Osteoarthritis Progressionmentioning
confidence: 95%
“…To account for these observations, we recently recorded detailed motion data via an optoelectronic motion capturing system, of the same subjects included in this study performing the actions investigated by Fukutani and colleagues (Fukutani et al, 2016), i.e. walking on a flat surface (Verlaan et al, submitted), ascending and descending stairs (Verlaan et al, 2019) and sit-to-stand (Verlaan et al, 2018) and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…To account for these observations, we recently recorded detailed motion data via an optoelectronic motion capturing system, of the same subjects included in this study performing the actions investigated by Fukutani and colleagues 57 , i.e. walking on a flat surface (Verlaan et al, submitted), ascending and descending stairs 58 and sit-to-stand 42 and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…56 Physical activity is an important determinant of general health and is negatively affected by many chronic degenerative diseases. 57,58 The increased mortality documented for untreated hip OA is attributed to reduced physical activity. 59 Knee OA will have the same results.…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation